2022
DOI: 10.1128/msystems.00827-22
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Assessment of Clinical Escherichia coli Isolates as an Indicator for Uropathogenic Potential

Abstract: Urinary tract infections are the second leading infectious disease worldwide, occurring in over half of the female population during their lifetime. Most infections are caused by uropathogenic Escherichia coli (UPEC) strains.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 66 publications
2
13
3
Order By: Relevance
“…However, a similar study comparing UTI clinical isolates of several sequence types, found multiple isolates were nonmotile after 16 hours at 30°C with an equal number hypermobile as compared to CFT073; whereas, our study found most clinical isolates more motile than CFT073, with only 3/20 isolates less motile than the lab strain BW25113 or pathogenic CFT073 [14]. The same study found most clinical isolates tested produced less biofilm than CFT073 at 37°C; whereas, in our study we found CFT073 to be comparable to the ST131 clinical isolates yet lower than the lab strains for both static and shaking conditions [14]. The only ST131 isolate tested (HM6) also showed comparable biofilm production to CFT073 in the previous study [14].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, a similar study comparing UTI clinical isolates of several sequence types, found multiple isolates were nonmotile after 16 hours at 30°C with an equal number hypermobile as compared to CFT073; whereas, our study found most clinical isolates more motile than CFT073, with only 3/20 isolates less motile than the lab strain BW25113 or pathogenic CFT073 [14]. The same study found most clinical isolates tested produced less biofilm than CFT073 at 37°C; whereas, in our study we found CFT073 to be comparable to the ST131 clinical isolates yet lower than the lab strains for both static and shaking conditions [14]. The only ST131 isolate tested (HM6) also showed comparable biofilm production to CFT073 in the previous study [14].…”
Section: Discussioncontrasting
confidence: 65%
“…The same study found most clinical isolates tested produced less biofilm than CFT073 at 37°C; whereas, in our study we found CFT073 to be comparable to the ST131 clinical isolates yet lower than the lab strains for both static and shaking conditions [14]. The only ST131 isolate tested (HM6) also showed comparable biofilm production to CFT073 in the previous study [14]. These differences could be due to the divergence of experimental parameters with different temperatures and assay times but are also reflective of the variable nature of clinical isolates in phenotypic testing as noted throughout this paper.…”
Section: Discussioncontrasting
confidence: 62%
“…When physiological balance is disturbed by disease, surgery, medication, a wound, a foreign body, immunodeficiency, or other circumstance, some commensal organisms coexisting with their human host become opportunistic pathogens. 1 Examples of commensal bacteria that are opportunistic pathogens include Streptococcus pneumoniae (S. pneumoniae), Staphylococcus aureus (S. aureus), uropathogenic Escherichia coli (E. coli, UPEC, motile from the intestine to the urethra), 2 and those from the environment such as Pseudomonas aeruginosa (P. aeruginosa). 3 Opportunistic pathogens readily adhere to hydrophobic silicone and form biofilms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…aureus), uropathogenic Escherichia coli (E. coli, UPEC, motile from the intestine to the urethra), and those from the environment such as Pseudomonas aeruginosa (P. aeruginosa) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation